Sustainable transportation on university campus: a case at UiTM Selangor, Puncak Alam campus, Malaysia and Universitas Negeri Semarang, Indonesia / Veera Pandiyan Kaliani Sundram ... [et al.] - Kaliani Sundram, Veera Pandiyan; Hashim, Nurhazirah; Shariff, Siti Halijjah; Pujiati, Amin; Ardiansari, Anindya (Universiti Teknologi MARA, 2021)
The increased awareness of the impact of carbon dioxide (CO2) emissions and consumption of fossil fuels on the environment has led to world-wide research focused on sustainable transportation solutions. University campuses are one of the affected environments involved in this issue as a high dependency on private vehicles causes' traffic congestion in the campus area particularly during peak hours leading to concerns about parking especially for the established universities. Therefore, alternative transport solutions should be considered in minimizing the environmental consequences specifically within the campus area. This study aims to examine the extent of sustainable transportation practices implemented by a university campus in a developing country, Malaysia and Indonesia. A survey methodology was applied using self-administered questionnaires as the main technique of data collection. Both, UiTM Puncak Alam, Selangor, Malaysia and Universitas Negeri Semarang, Indonesia are selected as the sample study and the target observations are focused on the transportation pathway which includes transportation modes, passengers, terminal and parking space. The study is expected to enrich the existing sustainable model of Stakeholder Theory to deliver a more robust competency model to provide solutions in creating sustainable transportation in university campuses. Subsequently, the outcome would support Sustainable Development Goals (SDGs 2030), Mid-term Review of the Eleventh Malaysia Plan [2016 - 2020], Indonesia's long-term development plan to phase IV period 2020-2025 through better adoption of low- carbon supply chain practices in order to reduce GHG emission. This is in line with Malaysia and Indonesia's commitment in being a key part of the global transition to a low-carbon, and eventually carbon- neutral society by 2050